2011
DOI: 10.1177/1049732311424404
|View full text |Cite
|
Sign up to set email alerts
|

Sources of the Uncertainty Experienced by Women With HPV

Abstract: Women with genital human papillomavirus (HPV) experience considerable stress and uncertainty as a result of the diagnosis; however, little is known about the sources of uncertainty in HPV. Given that uncertainty creates stress, which might be linked to the pathogenesis of cervical cancer, research on these sources of uncertainty is warranted. To this end, we completed semistructured interviews with 25 women living with HPV, and identified seven sources of uncertainty: The meaning of the diagnosis, the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 44 publications
6
37
0
Order By: Relevance
“…Prior research has established that, for patients, the experience of illness tends to be accompanied by uncertainty (e.g., Babrow, Kasch, & Ford, 1998;Brashers et al, 2003;Kosenko, Hurley, & Harvey, 2011;Martin, Stone, Scott, & Brashers, 2010;Mishel, 1988Mishel, , 1990. Less commonly, the uncertainty of a patient's loved ones has been documented (e.g., Donovan-Kicken & Bute, 2008;Goldsmith, 2009;Stone & Jones, 2009).…”
Section: Partners' Experience Of Caregivingmentioning
confidence: 96%
“…Prior research has established that, for patients, the experience of illness tends to be accompanied by uncertainty (e.g., Babrow, Kasch, & Ford, 1998;Brashers et al, 2003;Kosenko, Hurley, & Harvey, 2011;Martin, Stone, Scott, & Brashers, 2010;Mishel, 1988Mishel, , 1990. Less commonly, the uncertainty of a patient's loved ones has been documented (e.g., Donovan-Kicken & Bute, 2008;Goldsmith, 2009;Stone & Jones, 2009).…”
Section: Partners' Experience Of Caregivingmentioning
confidence: 96%
“…Uncertainty around positive-HPV test results is high (Kosenko, Hurley, & Harvey, 2012): such as its meaning and separation from other diseases, such as herpes, its progression, and the source of infection. In contrast, HPV has few visible symptoms that are likely to be unintentionally noticed, which may lower symptoms’ salience.…”
Section: Initial Conversations About Positive Hpv Test Resultsmentioning
confidence: 99%
“…The results in this study showed that the relational concerns may infuse the disclosure and initial reactions by attempting to get and give reassurance that the diagnosed person is not tainted by the health condition and their interpersonal relationship remains strong. Tensions between social rejection and disclosure have been reported by women living with HPV (Kosenko, Hurley, & Harvey, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…As blog members share their information with each other, it is possible that they could become even more confused or misinformed. Misinformation can be a source of uncertainty for individuals with HPV, which can impact coping, disclosure, and thus psychological adjustment [Kosenko, Hurley, & Harvey, 2012]. These findings demonstrate a need for people diagnosed with HPV to be given more accurate and thorough information in a way that is understandable.…”
Section: Discussionmentioning
confidence: 99%